Pengaruh Kampanye Instagram Greenpeace Indonesia terhadap Perilaku Pro-Lingkungan: Mediasi Emosi dan Kesadaran - Rafa, Ersa Nabalah; Pamungkas, Yoma Bagus; Saptiyono, Ami (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study aims to examine the influence of Greenpeace Indonesia's Instagram campaign on the pro-environmental behavior of the younger generation by highlighting the mediating role of ecological emotions and environmental awareness. Using a quantitative approach and the Generalized Structured Component Analysis (GSCA) method, this study involved 384 respondents aged 17–35 years who were active followers of @greenpeaceid accounts. The results of the analysis showed that Greenpeace Indonesia's digital campaign had a significant direct effect on pro-environmental behavior (β = 0.298; p 0.001). In addition, ecological emotions (β = 0.133; Z = 4.83) and environmental awareness (β = 0.139; Z = 6.06) was shown to partially mediate the relationship. These findings strengthen the integration of four main theories, namely the Elaboration Likelihood Model (ELM), Theory of Planned Behavior (TPB), Affective Response Theory (ART), and Value-Belief-Norm Theory (VBN), as a conceptual framework to understand the mechanism of behavior change based on social media campaigns. Theoretically, the study enriches the environmental communication literature by emphasizing the importance of emotional and cognitive aspects in the effectiveness of digital campaigns. By practical implication, environmental organizations and policymakers are advised to design communication strategies that combine emotional and educational visual elements to increase public awareness and engagement in sustainable pro-environmental action.